2019
DOI: 10.1016/j.scog.2019.100158
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of occupational outcome in recent-onset psychosis: The role of cognition

Abstract: Working or studying is a common goal among people with recent-onset psychosis. Cognitive deficits have been reported to influence occupational outcome, but to date few studies have evaluated if cognitive deficits independently predict occupational outcome when taking into account other important determinants, such as self-esteem, motivation, length of time absent from employment/school, job/school search behaviours, subjective cognitive complaints and psychotic symptoms. Hence, this longitudinal study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 64 publications
(81 reference statements)
0
8
0
1
Order By: Relevance
“…Furthermore, our results would emphasize that social embedding and social support are critical for mental health protection and that well-being during real-life social contact is linked to social resilience in individuals PD with CM (Gan et al, 2021). Given that sequelae of CM may affect the ability to engage in both attachment and therapeutic relationships (Picken, Berry, Tarrier, & Barrowclough, 2010), our review on the association between CM and social functioning in PD is therefore a major concern for therapy delivery (MaBeth, Gumley, Schwannauer, & Fisher, 2011).…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, our results would emphasize that social embedding and social support are critical for mental health protection and that well-being during real-life social contact is linked to social resilience in individuals PD with CM (Gan et al, 2021). Given that sequelae of CM may affect the ability to engage in both attachment and therapeutic relationships (Picken, Berry, Tarrier, & Barrowclough, 2010), our review on the association between CM and social functioning in PD is therefore a major concern for therapy delivery (MaBeth, Gumley, Schwannauer, & Fisher, 2011).…”
Section: Discussionmentioning
confidence: 73%
“…HCRU has been shown to be associated with working memory, verbal memory, and executive function ( Hori et al, 2020 ). Working memory and verbal memory have also been directly associated with employment and independent living, respectively ( Pothier et al, 2019 ; Shamsi et al, 2011 ). Multiple aspects of cognition have been associated with QoL ( Pascal de Raykeer et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with previous reports indicating that processing speed impairment is related to schizophrenia [ 9 11 ] and FEP [ 13 ]. Furthermore, two longitudinal studies revealed that processing speed is linked to subsequent functional outcomes [ 16 ], including occupational status [ 20 ]. This evidence emphasizes that processing speed deficits are a potential intervention target to obtain better functional outcomes in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…These impairments have been observed even in first-episode psychosis (FEP) [13,14]. Furthermore, cognitive impairment is related to poor functional outcomes [15][16][17], such as occupational prognosis, in schizophrenia [15,[18][19][20]. Importantly, therapeutic interventions targeting cognitive deficits have shown great success not only in the improvement of cognitive function [21,22] but also in better functional outcomes [23], including occupational conditions [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%